Competition policy at war with industrial policy? - Andreas Strohm (EIB Papers, 2006)
Competition policy has seen quite significant changes over the past years. With the reform of Merger Control and the application of Article 81 (agreements) an 'effects-based, economic approach' was formally introduced by the Commission. Two other areas of competition policy are under discussion, namely state aid control and the application of Article 82 (abuse of a dominant position). It will be one of the key questions whether and to what extent an 'economic approach' should be followed here too. Some issues of competition policy with regard to industrial policy will be analysed in view of this changes. As the 'economic approach' is based on neoclassical market form analysis and welfare economics, I will try to make these approaches more comprehensive before I point to some problems which occur if the 'theory' were to be applied in real cases.
Keywords: 330; Industriepolitik; Wettbewerbspolitik; Wirtschaftspolitisches Ziel; Subvention; EU-Staaten